Development and assessment of novel virtual COVID-19 trainer-of trainers course implemented by an academic-humanitarian partnership - Ramu Kharel; Janette Baird; Himanshu Vaishnav; Nidhi Chillara; J. Austin Lee; Alicia Genisca; Alison Hayward; Vlatko Uzevski; Asmaa Elbenni; Adam C. Levine; Adam R. Aluisio (Taylor & Francis Group, 2022)
Background In response to the coronavirus disease (COVID-19) pandemic, Project HOPE®, an international humanitarian organization, partnered with Brown University to develop and deploy a virtual training-of-trainers (TOT) program to provide practical knowledge to healthcare stakeholders. This study is designed to evaluate this TOT program. Objective The goal of this study is to assess the effectiveness of this educational intervention in enhancing knowledge on COVID-19 concepts and to present relative change in score of each competency domains of the training. Methods The training was created by interdisciplinary faculty from Brown University and delivered virtually. Training included eight COVID-19 specific modules on infection prevention and control, screening and triage, diagnosis and management, stabilization and resuscitation, surge capacity, surveillance, and risk communication and community education. The assessment of knowledge attainment in each of the course competency domain was conducted using 10 question pre-and post-test evaluations. Paired t-test were used to compare interval knowledge scores in the overall cohort and stratified by WHO regions. TOT dissemination data was collected from in-country partners by Project Hope. Results Over the period of 7 months, 4,291 personnel completed the TOT training in 55 countries, including all WHO regions. Pre-test and post-test were completed by 1,198 and 706 primary training participants, respectively. The mean scores on the pre-test and post-test were 68.45% and 81.4%, respectively. The mean change in score was 11.72%, with P value <0.0005. All WHO regions had a statistically significant improvement in their score in post-test. The training was disseminated to 97,809 health workers through local secondary training. Conclusion Innovative educational tools resulted in improvement in knowledge related to the COVID-19 pandemic, significantly increasing the average score on knowledge assessment testing. Academic - humanitarian partnerships can serve to implement and disseminate effective education rapidly across the globe.